Integral life buoy with gradient hollow lattice structure and manufacturing method of integral life buoy

Through selective laser sintering technology, the integrated lifebuoy with a gradient hollow lattice structure is manufactured, combined with polypropylene composite powder and specific fillers, the problems of lifebuoy material separation and easy damage are solved, and high strength, high buoyancy and long life are achieved Effect.

CN119220016APending Publication Date: 2024-12-31OECHSLER PLASTIC PROD TAICANG +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411354929.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

When existing lifebuoys are impacted or exposed to outdoor environments for a long time, the outer layer material and the core material are easily partially separated or disconnected, resulting in a short service life. The inflatable lifebuoys are easily damaged, which is suitable for temporary use but not for long-term use. .

Method used

Selective laser sintering technology (SLS) is used to manufacture an integral lifebuoy with a gradient hollow lattice structure, using polypropylene composite powder as raw material, and the internal hollow structure is combined with the external dense structure to increase elastomer and borosilicate glass Hollow microbeads and nanotitanium dioxide/kaolin nanotube fillers to improve impact performance and buoyancy.

Benefits of technology

It realizes the excellent characteristics of lifebuoy with light weight, high buoyancy, high strength, impact resistance and long service life, extends the service lifebuoy and improves its application performance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220016A_ABST
    Figure CN119220016A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of manufacturing of high-performance life buoys, in particular to an integral life buoy with a gradient hollow lattice structure and a manufacturing method of the integral life buoy. According to the invention, polypropylene powder is used as a raw material, and the integral life buoy with the gradient hollow lattice structure is formed at one time by using a selective laser sintering technology. The impact toughness, the mechanical strength and the buoyancy of the integral life buoy can be effectively improved by adding the nano TiO2 / HNT hybrid prepared by a hydrothermal method, the elastomer powder and the borosilicate glass hollow microspheres into the polypropylene composite powder and utilizing the gradient hollow lattice structure of the integral life buoy; and the service life of the life buoy can be effectively prolonged by the integral structure. The integral life buoy is simple in manufacturing process, high in cost benefit and beneficial to large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The technology of the present invention relates to the technical field of high-performance lifebuoy manufacturing, and specifically to an integral lifebuoy with a gradient hollow lattice structure and a manufacturing method thereof. Background Art

[0002] Lifebuoys are a type of water lifesaving equipment, usually placed on the deck and sides of water transport ships, and also placed near waters such as the shore of urban waters, bridge guardrails, and the entrances of rivers and ponds. Lakes are an important part of urban public waters. There are many lakes in my country, with a total area of ​​78,007.1 square kilometers. With the increase in the construction of water-related scenic spots in urban areas and the increasing frequency of water-related activities by residents, the probability of people falling into the water is also increasing accordingly. At the same time, the passenger and cargo transportation volume on both the ocean and lakes and rivers is increasing year by year. Ships are widely used in water transportation, sightseeing and various engineering tasks. Lifebuoys are indispensable safety equipment for these ships when sailing. In addition, the relevant departments have gradually increased their supervision of water safety, and improved the placement standards and number of water safety rescue facilities. Due to the above reasons, although the configuration of lifebuoys varies in different regions and occasions, they are generally increasing.

[0003] Conventional lifebuoys are usually made of cork, foam plastic or other lightweight materials with low specific gravity as the core material, and then covered with canvas, plastic and other materials on the outside of the core material. However, when this split lifebuoy encounters an impact or is exposed to the outdoor environment for a long time, the outer layer material may be partially or completely separated from the core material, which seriously affects its use effect and lifespan.

[0004] Currently, most of the existing integrated lifebuoys are inflatable lifebuoys, with the surface material of polyester fiber. They need to be inflated during use. Over-inflation is prone to cracking due to excessive cold or overheating of the external environment, which affects the service life. In addition, inflatable lifebuoys are also easily punctured by sharp objects, or leak due to large impact force, and lose their function. Therefore, inflatable lifebuoys are more suitable for temporary life-saving equipment in emergency situations, but not suitable for long-term use. Summary of the invention

[0005] In view of the fact that the existing lifebuoys for long-term use are usually made of cork, foam plastic or other light materials with low specific gravity, and are covered with canvas, plastic, etc., when subjected to strong external impact or placed in an open-air environment for too long, it is easy to cause the outermost coating material to separate from the inner core material of the lifebuoy, resulting in a short service life. The present invention proposes an integral lifebuoy with a gradient hollow lattice structure and a manufacturing method thereof, the purpose of which is to manufacture the integral lifebuoy in one-time molding, and to make the integral lifebuoy have excellent characteristics such as light weight, high buoyancy, high strength, impact resistance, and long service life.

[0006] The solution of the present invention uses selective laser sintering (SLS) technology as a preparation process, first preparing a polypropylene composite powder, and then using the polypropylene composite powder as a raw material for the SLS technology to prepare a high-strength and high-buoyancy integral lifebuoy with a gradient hollow lattice structure. The present invention utilizes a lattice structure to manufacture a lifebuoy, which can have the advantages of light weight and high strength at the same time. The present invention utilizes the selective laser sintering technology (SLS) in 3D printing technology to directly form an integral lifebuoy with a gradient hollow lattice structure inside and a dense structure on the outside. Polypropylene is a polymer obtained by propylene addition polymerization, and has a density of 0.89 to 0.91 g / cm 3 It has good chemical resistance, moisture resistance, non-toxicity, mechanical properties and molding processing performance. It can be SLS printed and can withstand the harsh use scenarios of lifebuoys.

[0007] The method for manufacturing an integral lifebuoy with a gradient hollow lattice structure of the present invention uses polypropylene-based composite powder as a raw material and selectively laser sintering to form an integral lifebuoy with a hollow lattice inside and a dense solid skin layer outside, wherein the lattice size of the internal hollow lattice increases from the outside to the inside;

[0008] Polypropylene-based composite powder includes the following components:

[0009] Polypropylene powder, 100-120 parts by mass;

[0010] Elastomer powder, 10-20 parts by mass;

[0011] Borosilicate glass hollow microspheres, 4 to 12 parts by weight;

[0012] Nano-titanium dioxide / kaolin nanotube (nano-TiO2 / HNT) hybrid, 3 to 9 parts by mass;

[0013] Antioxidant, 0.5-1.5 parts by weight;

[0014] Ultraviolet light absorber, 0.3 to 0.5 parts by weight.

[0015] In the scheme of the present invention, the life buoy is formed by selective laser sintering of polypropylene-based composite powder, elastomer powder is mixed into pure polypropylene powder to achieve toughening effect, borosilicate glass hollow microspheres are mixed to achieve light weight and high buoyancy effect, and an inorganic hybrid filler is synthesized with nano-TiO2 and kaolin carbon nanotubes as raw materials and mixed into polypropylene powder to improve impact resistance and heat resistance. The internal gradient hollow structure of the life buoy can reduce the weight of the life buoy while providing good mechanical properties, thereby improving buoyancy. The integral life buoy with a gradient hollow lattice structure thus obtained is light and high-strength, has high buoyancy, and has a long service life, while meeting the requirements of the integral type, and has good application prospects.

[0016] As a further optimization scheme, the elastomer powder is one or more of ethylene-vinyl acetate copolymer (EVA) powder, styrene-butadiene-styrene block copolymer (SBS resin) powder, and polyamide thermoplastic elastomer (TPEA) powder.

[0017] As a further optimization scheme, borosilicate glass hollow microspheres with a particle size of 10 to 50 μm and surface modified with a silane coupling agent include the following steps: 4 to 12 parts by mass of borosilicate glass hollow microspheres are uniformly dispersed in 100 parts by mass of an ethanol solution, the temperature is raised to 60 to 80° C., and stirring is continued for 30 to 60 minutes. 0.5 to 1.5 parts by mass of a silane coupling agent is added thereto, stirring is continued for 30 to 60 minutes, suction is filtered, and drying is performed to obtain modified borosilicate glass hollow microspheres.

[0018] As a further optimization scheme, nano-titanium dioxide / kaolin nanotube (nano-TiO2 / HNT) hybrids were prepared by hydrothermal method, including the following preparation steps:

[0019] Step 1.1: Pour 2 to 5 parts by mass of nano-TiO2 and 2 to 5 parts by mass of HNT into a sodium hydroxide solution, stir evenly, pour into a polytetrafluoroethylene reactor, react at 130 to 180° C. for 8 to 12 hours, and collect to obtain a solid powder; the particle size of the nano-TiO2 is 10 to 20 nm, and the specifications of the kaolin nanotubes are an inner diameter of 10 to 80 nm, an outer diameter of 30 to 100 nm, and a tube length of 0.02 to 10 μm;

[0020] Step 1.2: The solid powder obtained in step 1.1 is washed with distilled water for 2 to 3 times, immersed in hydrochloric acid for 30 to 60 minutes, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0021] As a further optimization scheme, the antioxidant is one or more of a semi-hindered phenol antioxidant, a phosphite antioxidant, a sterically hindered phenol antioxidant and a thermally stable antioxidant.

[0022] As a further optimization scheme, the ultraviolet light absorber is one or more of hydroquinone, 2-dihydroxy-4-methoxybenzophenone and 2-hydroxy-4-octyloxybenzophenone.

[0023] As a further optimization scheme, the preparation of polypropylene composite powder includes the following steps:

[0024] Step 2.1: 100 to 120 parts by weight of polypropylene powder, 10 to 20 parts by weight of elastomer powder, 4 to 12 parts by weight of borosilicate hollow microspheres, and 3 to 9 parts by weight of nano-TiO2 / HNT hybrid are placed in a constant temperature drying oven for complete drying;

[0025] Step 2.2: Mix the dried polypropylene powder, elastomer powder, borosilicate glass hollow microspheres, nano-TiO2 / HNT hybrid, 0.5-1.5 parts by weight of antioxidant and 0.3-0.5 parts by weight of ultraviolet light absorber in a high-speed mixer to obtain a polypropylene composite powder.

[0026] The integral life buoy with a gradient hollow lattice structure provided by the present invention comprises an internal hollow lattice and a dense solid epidermis layer on the surface, wherein the hollow lattice and the dense solid epidermis layer are integrally formed; the lattice size of the internal hollow lattice increases from the outside to the inside; when printing, the dense solid epidermis layer is provided with a circular hole for cleaning powder, and a hole cover is printed at the same time, and after the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting; the integral life buoy is formed by selective laser sintering using polypropylene-based composite powder as a raw material.

[0027] Preferably, the dense solid skin layer forms a closed curved solid on the surface of the outer cell of the hollow lattice, with a thickness of 0.2 to 0.5 cm, and circular holes with a diameter of 5 cm and a thickness of 0.2 to 0.5 cm are left on the dense skin layer, and the hole covers are printed at the same time.

[0028] Preferably, the shape and size of the hole cover are consistent with the circular hole, and the structure after the two are closed is consistent with the closed curved surface entity of the outer cell surface.

[0029] Preferably, the internal hollow lattice is composed of a plurality of cells, the cells include a frame forming a closed polygon, cell ribs located within the frame, and a hollow cavity is formed between the frame and the cell ribs; the size of the cells increases gradiently from the outer layer to the inner layer; and the diameter of the cell rod decreases gradiently from the outermost layer to the inner layer.

[0030] Beneficial Effects

[0031] (1) The solution of the present invention is based on SLS technology, using polypropylene as raw material, and a high-strength and high-buoyancy integral lifebuoy with a gradient hollow lattice structure is obtained by one-step molding. The preparation method is highly operable, and the gradient hollow structure can reduce the mass of the lifebuoy while providing good mechanical properties, thereby improving the buoyancy. The integral lifebuoy has a prolonged service life on the basis of high strength and high buoyancy.

[0032] (2) In the scheme of the present invention, a hydrothermal method is used to prepare nano-TiO2 / HNT hybrids as reinforcing fillers in polypropylene composite powders, thereby improving the impact resistance, heat resistance and creep resistance of the integral lifebuoy. The synthesis method is simple and has practical applicability.

[0033] (3) The scheme of the present invention adds borosilicate glass hollow microspheres to the polypropylene composite powder. The spherical structure has good fluidity and can be used as a flow aid in SLS printing technology, which is conducive to the uniform distribution of the polypropylene composite powder. The hollow microspheres have good heat resistance and can effectively improve the heat resistance of the integral life buoy. At the same time, due to its special hollow structure, it can also play a good role in reducing mass and improving buoyancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of the overall structure of the life buoy.

[0035] Figure 2 for Figure 1 Schematic diagram of the cross section of section A.

[0036] Figure 3 Schematic diagram of the multi-layer structure of a lifebuoy cross section. DETAILED DESCRIPTION

[0037] The present application is further described below in conjunction with specific embodiments. These embodiments are exemplary and are intended to illustrate the problem and explain the present invention, and are not intended to be limiting.

[0038] Figure 1 The overall structure of the life buoy is shown. Figure 2 for Figure 1 Schematic diagram of the cross section of section A. Figure 3The multilayer structure of the cross section of the life buoy is shown. The figure shows that there is a central unit cell 1 in the center of the life buoy, and the central unit cell 1 has the largest size, which is 6cm×6cm×6cm. From the central unit cell 1 to the outside, it includes the second coating unit cell layer 2, the third coating unit cell layer 3, the fourth coating unit cell layer 4, the fifth coating unit cell layer 5 and the continuous solid epidermis layer 6. The unit cell sizes of the second coating unit cell layer 2, the third coating unit cell layer 3, and the fourth coating unit cell layer 4 are 5cm×5cm×5cm, 4cm×4cm×4cm, and 3cm×3cm×3cm, respectively. The fifth coating unit cell layer 5 is a near-surface layer with a unit cell size of 2cm×2cm×2cm. The unit cell size of each unit cell structure layer decreases gradually in a gradient. The epidermis layer 6 is a continuous solid layered structure with a thickness of 0.2 to 0.5cm.

[0039] Example 1

[0040] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0041] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 4 g of glass hollow microspheres K110, 3 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0042] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy with a 5 cm diameter powder cleaning round hole and a powder cleaning hole cover were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 99.9% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface have the same volume, and the total volume ratio is 0%, and the hollow unit cell layer 5 near the surface accounts for 0% of the volume.

[0043] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0044] Example 2

[0045] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0046] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 3 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0047] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy with a 5 cm diameter powder cleaning round hole and a powder cleaning hole cover were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 99.9% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface have the same volume, and the total volume ratio is 0%, and the hollow unit cell layer 5 near the surface accounts for 0% of the volume.

[0048] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0049] Example 3

[0050] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0051] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 12 g of glass hollow microspheres K110, 3 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0052] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy with a 5 cm diameter powder cleaning round hole and a powder cleaning hole cover were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 99.9% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface have the same volume, and the total volume ratio is 0%, and the hollow unit cell layer 5 near the surface accounts for 0% of the volume.

[0053] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0054] Example 4

[0055] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0056] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0057] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy with a 5 cm diameter powder cleaning round hole and a powder cleaning hole cover were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 99.9% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface have the same volume, and the total volume ratio is 0%, and the hollow unit cell layer 5 near the surface accounts for 0% of the volume.

[0058] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0059] Example 5

[0060] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0061] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 9 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0062] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy with a 5 cm diameter powder cleaning round hole and a powder cleaning hole cover were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 99.9% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface have the same volume, and the total volume ratio is 0%, and the hollow unit cell layer 5 near the surface accounts for 0% of the volume.

[0063] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0064] Example 6

[0065] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0066] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0067] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy and a powder cleaning hole cover with a diameter of 5 cm were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 66.6% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface have the same volume, with a total volume ratio of 33.3%, and the hollow unit cell layer 5 near the surface accounts for 0% of the volume.

[0068] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0069] Example 7

[0070] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0071] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0072] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy and a powder cleaning hole cover with a diameter of 5 cm were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 66.6% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface have the same volume, with a total volume ratio of 0%, and the hollow unit cell layer 5 near the surface accounts for 33.3% of the volume.

[0073] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0074] Example 8

[0075] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0076] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0077] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy and a powder cleaning hole cover with a diameter of 5 cm were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 was 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounted for 33.3% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface accounted for the same volume, with a total volume ratio of 66.6%, and the hollow unit cell layer 5 near the surface accounted for 0% of the volume.

[0078] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0079] Example 9

[0080] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0081] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0082] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy and a powder cleaning hole cover with a diameter of 5 cm were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 was 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounted for 33.3% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface accounted for the same volume, with a total volume ratio of 0%, and the hollow unit cell layer 5 near the surface accounted for 66.6% of the volume.

[0083] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0084] Example 10

[0085] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0086] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0087] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy and a powder cleaning hole cover with a diameter of 5 cm were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 was 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounted for 33.3% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface accounted for the same volume, with a total volume ratio of 33.3%, and the hollow unit cell layer 5 near the surface accounted for 33.3% of the volume.

[0088] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0089] Embodiment 11

[0090] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0091] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0092] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy with a 5 cm diameter powder cleaning round hole and a powder cleaning hole cover were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 0% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface account for the same volume, with a total volume ratio of 66.6%, and the hollow unit cell layer 5 near the surface accounts for 33.3% of the volume.

[0093] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0094] Example 12

[0095] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0096] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0097] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy and a powder cleaning hole cover with a diameter of 5 cm were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 was 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounted for 0% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface accounted for the same volume, with a total volume ratio of 33.3%, and the hollow unit cell layer 5 near the surface accounted for 66.6% of the volume.

[0098] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0099] Embodiment 13

[0100] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0101] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0102] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy with a 5 cm diameter powder cleaning round hole and a powder cleaning hole cover were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 0% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface have the same volume, with a total volume ratio of 99.9%, and the hollow unit cell layer 5 near the surface accounts for 0% of the volume.

[0103] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0104] Embodiment 14

[0105] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0106] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 6 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0107] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy with a 5 cm diameter powder cleaning round hole and a powder cleaning hole cover were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 is 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounts for 0% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface have the same volume, and the total volume ratio is 0%, and the hollow unit cell layer 5 near the surface accounts for 99.9% of the volume.

[0108] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0109] Comparative Example 1

[0110] (1) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 5 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0111] (2) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy and a powder cleaning hole cover with a diameter of 5 cm were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 was 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounted for 33.3% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface accounted for the same volume, with a total volume ratio of 33.3%, and the hollow unit cell layer 5 near the surface accounted for 33.3% of the volume.

[0112] (3) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillation with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0113] Comparative Example 2

[0114] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0115] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0116] (3) Using polypropylene composite powder as raw material, industrial-grade SLS equipment suitable for polymer materials was selected, and according to the printing model file programmed by CAD, a gradient hollow lattice structure lifebuoy and a powder cleaning hole cover with a diameter of 5 cm were printed respectively. In the programmed printing model file, the thickness of the skin layer 6 was 0.2 cm, accounting for 0.1% of the volume; in the unit cell structure, the central unit cell layer 1 accounted for 33.3% of the volume, and the hollow unit cell layers 2, 3, and 4 from the center to the near surface accounted for the same volume, with a total volume ratio of 33.3%, and the hollow unit cell layer 5 near the surface accounted for 33.3% of the volume.

[0117] (4) Powder cleaning is performed through the 5 cm diameter powder cleaning circular hole reserved in the epidermis, and the remaining powder in the life buoy is initially poured out, and then the remaining powder is further screened out by oscillating with an ultrasonic oscillator. After the powder cleaning is completed, the hole cover and the circular hole are closed and sealed by hot melting to obtain an integral life buoy with a gradient hollow lattice structure.

[0118] Comparative Example 3

[0119] (1) Pour 5g of nano-TiO2 and 5g of HNT into a sodium hydroxide solution and stir evenly, then pour into a polytetrafluoroethylene reactor and react at 150°C for 8h to obtain a solid powder. The solid powder is washed with distilled water for 3 times, immersed in hydrochloric acid for 30min, filtered, and then washed with distilled water until the pH value is 7, filtered, and dried to obtain a nano-TiO2 / HNT hybrid.

[0120] (2) 100 g of polypropylene powder, 15 g of ethylene-vinyl acetate copolymer, 8 g of glass hollow microspheres K110, 5 g of nano-TiO2 / HNT hybrid, 0.5 g of antioxidant 1076, and 0.3 g of hydroquinone were placed in a high-speed mixer and mixed for 40 min at a speed of 150 r / min to obtain a polypropylene composite powder.

[0121] (3) Using polypropylene composite powder as raw material, an industrial-grade SLS device suitable for polymer materials is selected, and a solid integral life buoy is printed according to the printing model file programmed by CAD.

[0122] Effect verification

[0123] The following performance tests were performed on the integral lifebuoys prepared in Examples 1 to 14 and Comparative Examples 1 to 3: The buoyancy of the lifebuoy was evaluated with reference to SOLAS 1974 / 1996 and GB4302-2008. The impact strength was evaluated with reference to GB / T 1043.1-2008, using a simply supported beam unnotched impact specimen. The tensile strength was evaluated with reference to GB / T 1040.3-2006, using a dumbbell type specimen at a tensile rate of 50 mm / min.

[0124] Table 1 Performance test results

[0125]

[0126] The results in Table 1 show that the test results of Examples 1 to 3 are to study the effects of different addition amounts of hollow glass microspheres K110 on the mechanical properties and buoyancy of the life buoy. Compared with Control Example 1 without adding hollow glass microspheres K110, the addition of hollow glass microspheres K110 significantly enhances the buoyancy of the life buoy, and with the increase in the addition amount of hollow glass microspheres K110, the tensile strength and impact strength are improved. The optimal addition amount of hollow glass microspheres K110 is 8g.

[0127] The test results of Example 2, Example 4 and Example 5 are to study the effects of different nano-TiO2 / HNT additions on the mechanical properties and buoyancy of the life buoy. Compared with the control example 2 without nano-TiO2 / HNT, as the amount of nano-TiO2 / HNT added gradually increases, the impact performance and tensile properties are improved, but too high an addition will cause the buoyancy to decrease. The main reason is that the density of nano-TiO2 / HNT is greater than the density of water. As the addition increases, the overall proportion of nano-TiO2 / HNT in the life buoy gradually increases, causing the buoyancy to decrease. Therefore, the optimal addition amount of nano-TiO2 / HNT is 6g.

[0128] The test results of Example 4 and Example 6 to Example 14 are to study the effects of different internal hollow lattice sizes on the mechanical properties and buoyancy of the high-strength and high-buoyancy integral lifebuoy. The central hollow cell structure is the largest cell structure in the whole, with a size of 6cm×6cm×6cm; the size of the hollow cell structure from the center to the near-surface layer decreases in sequence from 5cm×5cm×5cm, 4cm×4cm×4cm, and 3cm×3cm×3cm; the hollow cell structure near the surface is the smallest cell structure in the whole, with a size of 2cm×2cm×2cm. It can be seen from the examples that as the largest-sized cell structure gradually decreases and the smallest-sized cell structure gradually increases, the tensile strength and impact strength of the lifebuoy gradually increase. However, as the smallest-sized cell structure gradually increases, the buoyancy gradually decreases. The proportion of the central hollow cell structure, the central to near-surface hollow cell structure, and the near-surface hollow cell structure is 33.3%, that is, when the hollow structure inside the life buoy just presents a gradient decrease from the inside to the outside, the tensile strength is 38.94MPa, the impact strength is 10.02MPa at 23°C, and 4.90MPa at -20°C. At the same time, it also has a good buoyancy of 166.0N. Comprehensively considering the results of impact strength, tensile strength and buoyancy, Example 10 is the best group of embodiments. Compared with the completely dense life buoy in Control Example 3, it is shown that the lattice structure of the high-strength and high-buoyancy integral life buoy with a hollow lattice structure inside can enhance the impact strength and tensile strength while also greatly improving the buoyancy of the life buoy.

[0129] In summary, the integral lifebuoy with a gradient hollow lattice structure has good mechanical properties and high buoyancy, the integral structure can effectively extend the service life of the lifebuoy, the molding process is simple, and the manufacturing process is convenient and fast.

[0130] The above embodiments are exemplary, and their purpose is to illustrate the technical concept and features of the present invention so that people familiar with the technology in this field can understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for manufacturing an integral lifebuoy with a gradient hollow lattice structure, characterized in that: A monolithic lifebuoy having a hollow lattice inside and a dense solid skin layer outside is formed by selective laser sintering using polypropylene-based composite powder as raw material, wherein the lattice size of the hollow lattice inside increases from the outside to the inside; The polypropylene-based composite powder comprises the following components: Polypropylene powder, 100-120 parts by mass; Elastomer powder, 10-20 parts by mass; Borosilicate glass hollow microspheres, 4-12 parts by weight; Nano-titanium dioxide / kaolin nanotube (nano-TiO2 / HNT) hybrid, 3-9 parts by mass; Antioxidant, 0.5-1.5 parts by weight; Ultraviolet light absorber, 0.3~0.5 parts by mass.

2. The method for manufacturing a one-piece lifebuoy with a gradient hollow lattice structure according to claim 1, characterized in that: The elastomer powder is one or more of ethylene-vinyl acetate copolymer (EVA) powder, styrene-butadiene-styrene block copolymer (SBS resin) powder, and polyamide thermoplastic elastomer (TPEA) powder.

3. The method for manufacturing a monolithic lifebuoy having a gradient hollow lattice structure according to claim 1, characterized in that: The borosilicate glass hollow microspheres have a particle size of 10-50 μm and are surface-modified with a silane coupling agent, comprising the following steps: uniformly dispersing 4-12 parts by mass of the borosilicate glass hollow microspheres in 100 parts by mass of an ethanol solution, heating the solution to 60-80° C., stirring the solution for 30-60 minutes, adding 0.5-1.5 parts by mass of a silane coupling agent, stirring the solution for 30-60 minutes, filtering the solution with suction, and drying the solution to obtain modified borosilicate glass hollow microspheres.

4. The method for manufacturing an integral lifebuoy with a gradient hollow lattice structure according to claim 1, characterized in that: The nano titanium dioxide / kaolin nanotube (nano TiO2 / HNT) hybrid is prepared by a hydrothermal method, comprising the following preparation steps: Step 1.1: Pour 2-5 parts by mass of nano-TiO2 and 2-5 parts by mass of HNT into a sodium hydroxide solution, stir evenly, pour into a polytetrafluoroethylene reactor, react at 130-180° C. for 8-12 hours, and collect to obtain a solid powder; the particle size of the nano-TiO2 is 10-20 nm, and the specifications of the kaolin nanotubes are an inner diameter of 10-80 nm, an outer diameter of 30-100 nm, and a tube length of 0.02-10 μm; Step 1.2: The solid powder obtained in step 1.1 was washed with distilled water for 2 to 3 times, immersed in hydrochloric acid for 30 to 60 minutes, filtered, and then washed with distilled water until the pH value was 7, filtered, and dried to obtain nano-TiO2 / HNT hybrid.

5. The method for manufacturing an integral lifebuoy with a gradient hollow lattice structure according to claim 1, characterized in that: The antioxidant is one or more of a semi-hindered phenol antioxidant, a phosphite antioxidant, a sterically hindered phenol antioxidant and a thermally stable antioxidant.

6. The method for manufacturing an integral lifebuoy with a gradient hollow lattice structure according to claim 1, characterized in that: The ultraviolet light absorber is one or more of hydroquinone, 2-dihydroxy-4-methoxybenzophenone and 2-hydroxy-4-octyloxybenzophenone.

7. The method for manufacturing an integral lifebuoy with a gradient hollow lattice structure according to claim 1, characterized in that: The preparation of the polypropylene composite powder comprises the following steps: Step 2.1: 100-120 parts by weight of polypropylene powder, 10-20 parts by weight of elastomer powder, 4-12 parts by weight of borosilicate hollow microspheres, and 3-9 parts by weight of nano-TiO2 / HNT hybrid are placed in a constant temperature drying oven for complete drying; Step 2.2: The dried polypropylene powder, elastomer powder, borosilicate glass hollow microspheres, nano-TiO2 / HNT hybrid, 0.5-1.5 parts by weight of an antioxidant, and 0.3-0.5 parts by weight of an ultraviolet light absorber are mixed in a high-speed mixer to obtain a polypropylene composite powder.

8. A method for manufacturing an integral lifebuoy with a gradient hollow lattice structure according to any one of claims 1 to 7, characterized in that: When the life buoy is formed by selective laser sintering, a powder cleaning hole is left on the dense skin layer, and a hole cover is printed at the same time; the shape and size of the hole cover are consistent with the powder cleaning hole; After the powder cleaning is completed, the hole cover and the powder cleaning hole are closed and sealed by hot melting to form a closed surface entity consistent with the surface of the outer cell.

9. An integral lifebuoy with a gradient hollow lattice structure, characterized in that: It comprises a hollow lattice located inside and a dense solid skin layer located on the surface, wherein the hollow lattice and the dense solid skin layer are integrally formed; the lattice size of the hollow lattice inside increases from the outside to the inside; the integral lifebuoy is formed by selective laser sintering using polypropylene composite powder as raw material using the method described in claim 8.

10. The integral lifebuoy with a gradient hollow lattice structure according to claim 9, characterized in that: The dense solid epidermis layer shown forms a closed curved surface entity on the surface of the outer cell of the hollow lattice, with a thickness of 0.2~0.5cm; the internal hollow lattice is composed of multiple cells, and the cell includes a frame forming a closed polygon and cell tendons located in the frame, and a hollow cavity is formed between the frame and the cell tendons; the cell size increases gradiently from the outer layer to the inner layer; the cell rod diameter decreases gradiently from the outermost layer to the inner layer.